(3QSGdI JhHjN GdNGFH eMdGs - (3jMji Hf MeRI Hf Ydj Hf EHQGgje, GdMSjfj GdYdhqj GdWGdHj , GdeDjO HGddg , J (B745 (3g`s
(3ChdgG (B:s
(3GdQSGdI GdUGOQI Edi GdLeGYI HGSe GdEdg GdMGce GdehQK ebGdjO GdSehGJ hGdCQV def LYdg EeGekG gGOjkG s
(3BNQgG (B:s
(3aef CWGY adfaSg CSYO hef YUi adfaSg CPd hGHYO hGdMeO ddg hHg fSJYjf hgh fYe GdfUjQ GdeYjf s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B81s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
Keywords: (3GdJhMjO hGdedd hGdfMds